Effect of Dy3+ Concentrations on the Structural and Optical Properties of SrAl2O4:Eu2+, Dy3+ NPs - Kadenge, Victor; Kiprotich, Sharon; Kawira, Millien; Wako, Ali (Trends in Sciences, 2024)
Recently, there has been extensive research on the synthesis of luminescent particles, as these materials show great potential for various industrial uses. Multiple matrices have been formulated, with the SrAl2O4:Eu2+, Dy3+ matrix being the most extensively studied due to its superior optical and structural properties. In this work, the objective of synthesizing SrAl2O4:Eu2+, Dy3+ particles were achieved by using a combustion approach. By optimizing the synthesis process and studying the impact of Dy3+concentrations on the structural and optical features, it has proven feasible to regulate the reaction and attain exceptional optical characteristics. The importance of this investigation is in assessing the practical feasibility of using such a material. This study examines a phosphor composed of strontium aluminate (SrAl2O4) that is activated using various amounts of Dy3+(ranging from 0.1 to 0.8 mol %). The study’s findings of XRD showed that the SrAl2O4:Eu2+, Dy3+samples had a monoclinic phase of space group P21. Increase in the dopant concentration, the size of the crystallites in SrAl2O4:Eu2+, Dy3+ samples decreased, as determined by Scherer’s formula and the Williamson-Hall plot. The bandgap energy of doped SrAl2O4:Eu2+, Dy3+ nanoparticles was estimated using a Tauc plot based on data collected from an ultraviolet visible spectrophotometer. The results showed that the bandgap energy decreased from 6.5 to 5.5 eV as the level Dy3+rose from 0.1 to 0.8 mol %. FT-IR spectroscopy revealed a prominent vibrational stretching at 570 cm-1, which is likely due to the Al-O bond, and another stretching at 1049 cm-1, related to the Sr-O bonds of SrAl2O4:Eu2+, Dy3+ NPs. HIGHLIGHTS Optimizing the synthesis process and studying the impact of Dy3+concentrations on the structural and optical features, it has proven feasible to regulate the reaction and attain exceptional optical characteristics. The importance of this investigation is in assessing the practical feasibility of using such a material. GRAPHICAL ABSTRACT